Termite resistance of selected lesser-known Malaysian hardwoods - Wong, Andrew H.H; Grace, J. Kenneth (2014)
A combination of field and laboratory termite tests were used to evaluate the subterranean termite resistance of lesser-known tropical hardwoods from Malaysia, which have potential future use where termites pose problems to timber structures. The 28-day lab test followed the procedure of AWPA E1-97 subjecting mainly the heartwood of selected woods to either Coptotermes formosanus (in Hawai’i) and/or C. Curvignathus (Malaysia). Up to 22 hardwoods were evaluated. Test block mass losses and termite ratings were compared to show a range of termite resistance between wood species and in cases, within a single tree species occurred due to different degrees of atacks between these termites especially with rubberwood and kempas. Overall the most termite-resistant woods are notably: Burmese teak, Casuarina, Kekatong, Perah and Rengas (including surprisingly its sapwood) while notable perishable woods are: Carribbean pine, Scots pine, Acacia mangium and Albizia sp. Malaysian teak sustained moderate resistance, as were the woods Tualang, Sentang, Hoop pine, Kedondong, Kelat, mempening, Pauh Kijang and Keledang. Such findings contribute to the selection of wood species for structural applications aboveground indoor (or outdoor) with options for wood protection among the lesser-resistant woods.